CASE REPORT: EWING SARCOMA OF THE CHEST WALL - Vulovic, Dejan (Medicinski časopis, 2017)
Introduction Ewing Sarcoma, a highly malignant and poorly differentiated tumor, is composed of small round cells. Being the second most frequent tumor, it most commonly occurs in children and adolescents, with the gender ratio being 1.5:1 in favor of males. Location-wise, it most often occurs in the area of pelvis, knee, femur and humerus, whereas it is considerably less common in other bones, bones of the head, clavicle or ribs. According to EICESS studies, the forecast, along with adequate treatment, depends on the occurrence of distant metastases. Three-year survival rate of 66% was reported in patients in whom there were no secondary diseases. The emergence of a large volume tumor, which is primarily localized in the pelvis or the chest, has a poor prognosis. Case report In 2013, a boy born in 2005 presented with a pain in the chest. Upon performed biopsy and verified diagnosis, the case was presented to the Sarcoma Conference, and preoperative chemotherapy was conducted in accordance with the Euro Ewing 2008 protocol. As decided by the Sarcoma Conference, the resection was performed in 2013. The patient is regularly controlled and still without metastatic disease; fully rehabilitated. Discussion The above mentioned case report can lead us to conclude that a serious approach to all symptoms suffered by patients, some of which are often non-specific, is essential. All types of pain should be taken seriously and all necessary diagnostic testing should be immediately performed: to X-ray the affected area, and then, in case of suspected findings, to do a CT of the affected region, as well as skeletal scintigraphy. Tumors of the chest wall are rarely seen in children. Consistent application of the diagnostic system is none the less important than the subsequent approach to complete treatment. Surgical therapy must be aggressive to healthy resection surfaces, especially in relapses. Recurrence is not rare, and therefore surgical technique requires special attention. Ewing’s sarcoma serves as an example proving that only a multidisciplinary approach can result in an adequate diagnosis and treatment, as well as in providing patients with higher possibilities of final recovery. Key words: Ewing Sarcoma - diagnosis, treatment, thorax, bone tumors.